The African State in Transition
XVIII, 340 p.
Keywords: In the first twenty-five years of African independence the behaviour of the African state elites has not been, with a few notable exceptions, conducive to self-sustained development. What are the reasons for this sorry state of affairs? What can be done to reverse that unfortunate trend? These are the two overarching questions with which this book attempts to grapple.